The Impact of Central Government Spending on the 4K Program: Price Affordability, Supply Availability, Distribution, and Effective Communication, on Inflation in East Kalimantan - Wahono Wahono (FEB Universitas Mulawarman, 2025)
This study examines the impact of central government spending under the 4K Program-Price Affordability, Supply Availability, Smooth Distribution, and Effective Communication on inflation dynamics in East Kalimantan Province. Using monthly time series data covering the period 2023–2025, the analysis employs a time series regression framework to estimate both the direct effects of government spending on general inflation and the indirect effects transmitted through volatile food inflation. The results indicate that government spending on supply availability and distribution significantly reduces volatile food inflation, while spending on price affordability and effective communication shows limited impact. Furthermore, volatile food inflation has a positive and statistically significant effect on general inflation, confirming its role as a key mediation channel in fiscal transmission. The estimated indirect effects suggest that fiscal interventions primarily influence inflation through structural improvements in supply and distribution rather than through direct price interventions.These findings highlight the importance of channel-specific fiscal policy design. Prioritizing supply-oriented and distribution-enhancing expenditures is likely to produce more durable inflation-stabilizing effects, particularly in regions with high logistical dependence. This study contributes to the literature by providing empirical evidence on the transmission mechanisms of disaggregated fiscal spending at the regional level